A phase II investigator-initiated pilot study with low-dose cyclosporine A for the treatment of articular involvement in primary Sjögren's syndrome. Issue 9 (September 2016) - Kedor, Claudia; Zernicke, Jan; Hagemann, Anja; Gamboa, Lorena; Callhoff, Johanna; Burmester, Gerd-Rüdiger; Feist, Eugen
Abstract This study aims to investigate the efficacy and safety of low-dose cyclosporine A (CyA) in patients with primary Sjögren's syndrome (pSS) and articular involvement. This phase II open-label clinical study included 30 patients meeting the American-European Consensus group criteria for pSS with active joint involvement under stable symptomatic therapy. Treatment consisted of approximately 2 mg kg−1 body weight of CyA day−1 over a period of 16 weeks. The primary endpoint was defined as a reduction in the number of painful and/or swollen joints at end of treatment (EOT). Secondary endpoints included the changes in general health, sicca symptoms, European League Against Rheumatism (EULAR) Sjögren's Syndrome Disease Activity Index (ESSDAI), arthrosonography, and safety profile. At baseline (BL), the mean number of tender joints (68 count) was 16.2 (±13.2) and at EOT 10.4 (±11.9;p = 0.002). The mean number of swollen joints (66 counts) was reduced from 3.2 (±3.3) at BL to 1.3 (±3.2) at EOT (p < 0.001). Overall, 21 (70 %) and 13 (43.3 %) patients had a reduction of two or more tender and swollen joints, respectively, in the 68/66 joint counts. The disease activity score (DAS28) showed a statistically and clinically meaningful decrease over the 16-week period of treatment. Treatment was well tolerated, and adverse events were consistent with the known safety profile of CyA (e.g., hypertension, headache). In this pilot study, promising effects of low-dose CyA treatment on articular involvement were observed in patients with pSS justifying further controlled studies in this indication. No new or unexpected safety observations were made. Trial registration: Low-Dose Cyclosporin A in Primary Sjögren Syndrome (CYPRESS), ClinicalTrials.gov Identifier:NCT01693393 .